AIN coatings on silicon field emitters and oxidised gates to enhance reliability for space applications - Wang, L; Aplin, K; Kent, B; Huq, SE; Stevens, R; Thomas, G; Loader, I; Collingwood, C; Malik, A; Blom, H (2004)
The development of coatings for silicon field emission arrays used as an electron source to maintain spacecraft charge neutrality was described. The neutralizer specification included 6mA emission current at 0.2 W/mA and the instrument was required to operate for a lifetime of more than 6000 hours. In order to make the field emission device more resistant to ion bombardment and thermal failure, the effects of adding a layer of AlN, and thermal oxidation of the chromium gate electrode were investigated. A semi-automatic conditioning process, optimized for AlN coated devices was applied to each array before running at constant currents. It was found that once the device has been fully conditioned, the emission characteristic are permanent.